Kajian Kompetensi Pustakawan Terhadap Aksesibilitas Penyandang Disabilitas di Perpustakaan Perguruan Tinggi - Indriyani, Meyza; Safri, T. Mulkan; Fajarni, Suci (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This study aims to examine the competence of librarians towards the accessibility of persons with disabilities in university libraries. This type of research uses the library research method. The data collection method is carried out by studying and exploring relevant sources, such as: 1) collecting sources (books, articles/journals) studied, 2) reading, recording, and processing sources (books, articles/journals) studied. The results showed that the study of librarian competencies on the accessibility of persons with disabilities in higher education libraries is needed in providing and providing library services for people with disabilities, including competencies in the field of library management, competencies in the field of information technology, competencies in the field of communication, personality competencies, and competencies in sciences that support librarianship.————————————————————————————————Penelitian ini bertujuan untuk mengkaji kompetensi pustakawan terhadap aksesibilitas penyandang disabilitas di perpustakaan perguruan tinggi. Jenis penelitian menggunakan metode studi pustaka (library research). Metode pengumpulan data dilakukan dengan cara menelaah dan mengeksplorasi sumber yang relevan, seperti: 1) mengumpulkan sumber (buku, artikel/jurnal) yang dikaji, 2) dibaca, dicatat, dan diolah sumber (buku, artikel/jurnal) yang dikaji. Hasil penelitian menunjukkan bahwa kajian kompetensi pustakawan terhadap aksesibilitas penyandang disabilitas di perpustakaan perguruan tinggi sangat dibutuhkan dalam menyediakan dan memberikan pelayanan perpustakaan untuk pemustaka disabilitas, diantaranya kompetensi di bidang pengelolaan perpustakaan, kompetensi di bidang teknologi informasi, kompetensi di bidang komunikasi, kompetensi kepribadian, dan kompetensi ilmu-ilmu yang mendukung kepustakawanan.